Exploring the genetic and mechanistic basis of resistance to take-all disease in wheat - Osborne, Sarah-Jane (2017)
Take-all, caused by the soil-borne ascomycete fungus Gaeumannomyces graminis var. tritici, (Ggt), is a root disease that devastates wheat production worldwide. Current control measures consist of partially effective chemical seed dressings and cultural methods such as crop rotation. There is currently no genetic control of the disease. The first aim of this PhD project was to characterise a range of diploid and hexaploid wheat germplasm that possess a promising level of take-all resistance under field conditions. Both above and below ground phenotyping was carried out and soil moisture probes were used to evaluate upper root function for a range of hexaploid varieties. A diploid Triticum monococcum MDR037 (S) X MDR046 (R) mapping population was screened and revealed a good spread in susceptibility to take-all across two field seasons. The population has subsequently been genotyped and genetic analyses will be carried out to explore the genetic basis of resistance. Phialophora fungal species, belonging to the genus Gaeumannomyces, colonise wheat roots but do not destroy the vascular tissue and have previously been found to suppress take-all disease. In the second approach to control Ggt, winter wheat varieties on the AHDB Recommended List (RL) were screened for their ability to build-up natural populations of Phialophora fungi in the field. Differences were revealed in their potential to build-up Phialophora spp. under a first wheat crop. A Phialophora isolate collection was gathered and draft genomes were sequenced, assembled and annotated for the three Phialophora spp. found in UK soils. Preliminary analysis suggests that considerable polymorphism may exist between homologous genes found in all three species. These findings provide a novel contribution to the potential of these two differing control mechanisms against take-all disease.